2005
DOI: 10.1111/j.1365-2990.2005.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid injection of Microfil reveals connections between cerebrospinal fluid and nasal lymphatics in the non‐human primate

Abstract: Based on quantitative and qualitative studies in a variety of mammalian species, it would appear that a significant portion of cerebrospinal fluid (CSF) drainage is associated with transport along cranial and spinal nerves with absorption taking place into lymphatic vessels external to the central nervous system. CSF appears to convect primarily through the cribriform plate into lymphatics associated with the submucosa of the olfactory and respiratory epithelium. However, the significance of this pathway for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 46 publications
2
61
0
2
Order By: Relevance
“…Experimental results (Di Chiro, 1964;Orešković et al, 1991;Sato et al, 1972;Sato et al, 1971;Sato and Bering, 1967) also show that CSF is formed outside the brain ventricles (in subarachnoid space). The results also show that CSF absorption occurs not only through villi arachnoidales, but also inside the brain ventricles (Brightman, 1968;Bulat et al, 2008;Cserr, 1971;Dodge and Fishman, 1970;Foley, 1921;Hassin, 1924;Orešković et al, 1991;Wright, 1972), along the nerve roots (Kido et al, 1976), from the subarachnoid space into the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914), and high intraspinal absorption (Edsbagge et al, 2004).…”
Section: The New Working Hypothesis Of Cerebrospinal Fluid Hydrodynamicsmentioning
confidence: 87%
See 1 more Smart Citation
“…Experimental results (Di Chiro, 1964;Orešković et al, 1991;Sato et al, 1972;Sato et al, 1971;Sato and Bering, 1967) also show that CSF is formed outside the brain ventricles (in subarachnoid space). The results also show that CSF absorption occurs not only through villi arachnoidales, but also inside the brain ventricles (Brightman, 1968;Bulat et al, 2008;Cserr, 1971;Dodge and Fishman, 1970;Foley, 1921;Hassin, 1924;Orešković et al, 1991;Wright, 1972), along the nerve roots (Kido et al, 1976), from the subarachnoid space into the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914), and high intraspinal absorption (Edsbagge et al, 2004).…”
Section: The New Working Hypothesis Of Cerebrospinal Fluid Hydrodynamicsmentioning
confidence: 87%
“…Since Shabo and Maxwell (1968) showed that the observed tubular system was probably a consequence of tissue histological preparation, and that the endothelium of arachnoid villi was, in fact, intact (Shabo and Maxwell, 1968), Tripathi and Tripathi (1974) proposed that there are temporary transmesothelial channels which allow the passage of CSF in bulk flow from the subarachnoid space to the venous blood Tripathi and Tripathi, 1974). In addition, there is a large amount of literature which suggests that the significant absorption of CSF (Va) occurs from the subarachnoid space to the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914). Also, in spite of some other proposed places of CSF absorption (choroid plexuses, brain tissue, etc; see later), in physiological conditions the dural sinuses are still the main place of CSF absorption.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a large amount of literature which suggests that a significant amount of the absorption of CSF occurs from the subarachnoid space to the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Johnston et al, 2004;Koh et al, 2005;Koh et al, 2006;Weed, 1914). Also, despite some other proposed places (choroid plexuses, brain tissue, etc; see later), in physiological conditions the dural sinuses are still the main place of CSF absorption.…”
Section: Cerebrospinal Fluid Absorptionmentioning
confidence: 99%
“…Additionally, it is believed that the choroid plexuses are also the place of CSF absorption (Dodge and Fishman, 1970;Foley, 1921). Furthermore, there is a large amount of literature which suggests that significant CSF absorption occurs from the SAS to the lymphatic system (Bradbury, 1981;Brierly and Field, 1948;Dandy, 1929;Johnston et al, 2005;Koh et al, 2005;Koh et al, 2006;Weed, 1914). It was also described that CSF has an extrachoroidal origin (Hassin, 1924), and that it is formed, except in the ventricles, within the subarachnoid space (Sato and Bering, 1967;Sato et al, 1971;Sato et al, 1972).…”
Section: Classical Hypothesis and Controversial Experimental Datamentioning
confidence: 99%
“…It is believed that CSF is passively absorbed (under pressure gradient between CSF and blood) through arachnoid villi of the dural venous sinuses. In addition, there is a large amount of literature data which suggests that significant absorption of CSF from subarachnoid space to lymphatic system takes place (Johnston et al, 2004;Johnston et al, 2005;Koh et al, 2006). According to all above, it is generally accepted that CSF should flow unidirectionally (forced by pulsations of vessels) from brain ventricles to subarachnoid space with exchange of various substances (more or less manifested) between CSF and interstitial compartments (Johanson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%